2015
DOI: 10.2478/aoas-2014-0086
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the Fertility, Semen Quality, Blood Constituents, Immunity and Antioxidant Status of Rabbit Bucks to Type and Magnetizing of Water

Abstract: this work aimed to test the responses of the fertility, semen quality, blood constituents, immunity and antioxidant status of rabbit bucks to water type (e.g., tap water and well water) and magnetizing of water exposed or unexposed to a magnetic field of ≈4000 gauss. The experimental design was factorial 2 (type of water, e.g. tap vs. well water) × 2 (magnetic treatments, e.g. unexposed vs. exposed to magnetic field) using forty mature V-line rabbit bucks randomly distributed to four groups of 10 animals each.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 30 publications
6
50
1
Order By: Relevance
“…Exposed water showed considerable changes in its physicochemical characteristics, such as pH (8.69 vs 7.37 %), conductivity (9.83 vs 5.24 %), salinity (2.47 vs 9.69 %), Na (6.78 vs 15.78 %), Ca (15.02 vs 20.58 %), Mg (15.81 vs 20.08 %), Cl (27.05 vs 18.60 %), and dissolved oxygen (44.09 vs 37.07 %) of WW and TW, respectively, as published by Attia et al (2015). According to the literature, exposing water to magnetic fi elds changes its properties, with a slightly alkaline pH (>7), higher mineral (higher salinity) and oxygen contents, and lowers germs, which fulfi ls animal requirements for water quality (Mg-Therapy, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Exposed water showed considerable changes in its physicochemical characteristics, such as pH (8.69 vs 7.37 %), conductivity (9.83 vs 5.24 %), salinity (2.47 vs 9.69 %), Na (6.78 vs 15.78 %), Ca (15.02 vs 20.58 %), Mg (15.81 vs 20.08 %), Cl (27.05 vs 18.60 %), and dissolved oxygen (44.09 vs 37.07 %) of WW and TW, respectively, as published by Attia et al (2015). According to the literature, exposing water to magnetic fi elds changes its properties, with a slightly alkaline pH (>7), higher mineral (higher salinity) and oxygen contents, and lowers germs, which fulfi ls animal requirements for water quality (Mg-Therapy, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect on MPG matched the lower number of hatched goslings due to the low fertility and hatchability of fertile eggs, and as previously mentioned, could be attributed to decreased water consumption. Poor water quality has been shown to decrease animal performance and induce health risks (Wahaab and Badawy, 2004;Attia et al, 2013;2015). Moreover, De Blas (2013) reported that compositional alterations in the gut are a possible cause of gut disorders, retarded growth, and health problems in animals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations